Molecular characterization of the alpha subunit of complement component C8 (GcC8α) in the nurse shark (Ginglymostoma cirratum) - Aybar, Lydia (2009)
Target cell lysis by complement is achieved by the assembly and insertion of the membrane attack complex (MAC) composed of glycoproteins C5b through C9. The lytic activity of shark complement involves functional analogues of mammalian C8 and C9. Mammalian C8 is composed of α, β, and γ subunits. The subunit structure of shark C8 is not known. This report describes a 2341 nucleotide sequence that translates into a polypeptide of 589 amino acid residues, orthologue to mammalian C8α and has the same modular architecture with conserved cysteines forming the peptide bond backbone. The C8γ-binding cysteine is conserved in the perforin-like domain. Hydrophobicity profile indicates the presence of hydrophobic residues essential for membrane insertion. It shares 41.1% and 47.4 % identity with human and Xenopus C8α respectively. Southern blot analysis showed GcC8α exists as a single copy gene expressed in most tissues except the spleen with the liver being the main site of synthesis. Phylogenetic analysis places it in a clade with C8α orthologs and as a sister taxa to the Xenopus.